Verso un'estetica della macchina. Le nozioni di oggetto e di reale nella produzione artistica postmoderna (Nóema, 2011)
Il saggio esamina la pratica del ready-made nella scena artistica post-storica. Nel contesto di una ricodificazione del rapporto tra artistico e politico, i concetti di reale e oggetto veicolano una riflessione sul problema del realismo nella produzione Pop e Minimalista. Grazie ad una costellazione di autori (Lyotard, Deleuze e Guattari, Francastel, Lacan, Rancière) esploreremo il modo in cui il Postmoderno modula la propria impresa veritativa catturando atti extra-artistici e registrando l’emergenza di una dimensione macchinina. Towards an aesthetics of the machine.The notions of object and real in postmodernist artistic productionThis essay is conceived as a theoretical inquiry that seeks to examine ready-made practice as one of the most pertinent moments of the genesis of the post-historical artistic scene. In the framework of a recoded articulation of the art and the politics, concepts of Real and object will constitute the ground for a theoretical speculation on the question of realism in Pop Art and Minimalism. Thanks to a constellation of authors (Lyotard, Deleuze e Guattari, Francastel, Lacan, Rancière) we will explore how Postmodernism shapes its enterprise by “capturing” extra-artistic acts and how this intrusion implies the emergence of mechanical dimension.
Keywords: Postmodernismo artistico; Ready-made; Macchina; Ritorno del reale; Desimbolizzazione dell’oggetto; Dispositivo pulsionale; Libido; Traumatismo; Artistic Postmodernism; Machine; Return of the real; De-symbolization of the object; System of drive